2021
DOI: 10.3390/molecules26195878
|View full text |Cite
|
Sign up to set email alerts
|

Computational Screening of Natural Compounds for Identification of Potential Anti-Cancer Agents Targeting MCM7 Protein

Abstract: Minichromosome maintenance complex component 7 (MCM7) is involved in replicative licensing and the synthesis of DNA, and its overexpression is a fascinating biomarker for various cancer types. There is currently no effective agent that can prevent the development of cancer caused by the MCM7 protein. However, on the molecular level, inhibiting MCM7 lowers cancer-related cellular growth. With this purpose, this study screened 452 biogenic compounds extracted from the UEFS Natural Products dataset against MCM pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Cancer development is aided by the MCM7 protein, which is linked to tumor cell proliferation. A therapy approach for several human cancers is possible since the protein is extensively expressed during cancer development [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer development is aided by the MCM7 protein, which is linked to tumor cell proliferation. A therapy approach for several human cancers is possible since the protein is extensively expressed during cancer development [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer development is aided by the MCM7 protein, which is linked to tumor cell proliferation. A therapy approach for several human cancers is possible since the protein is extensively expressed during cancer development [46]. Medicinal plants have changed from fringe to mainstream usage in recent decades, and a growing number of individuals are seeking relief from herbal extracts [47].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Gahlawat et al (2020) screened inhibitors for the target main protease of SARS CoV-2; they used main protease inhibitors, natural products, and FDA-approved drugs [65]. The active site helps ligands to create enough contact sites to produce excellent interaction with the target protein by maintaining appropriate and desirable catalytic microenvironments [66][67][68][69]. In the ATP binding site of the NS3 helicase, the amino acids Glu231, Arg459, Gln455, Arg202, Glu286, Glu231, and Lys200 play a key role in the interaction with the ligands ellagic acid, hypericin, and pentagalloylglucose.…”
Section: Discussionmentioning
confidence: 99%
“…However, most recently inhibition of MCM2-7 activity by ciprofloxacin significantly delayed neuroendocrine prostate cancer (NEPC) cell growth and migration in vitro , exhibited potent anti-tumor effects in an NEPC xenograft model, and partially reversed neuroendocrine features ( 229 ). Alshahrani et al identified UEFS99, UEFS137 and UEFS428 as MCM7 inhibitors from the natural compounds databases using in silico computational screening, however further in vitro and in vivo studies are needed to validate target engagement ( 230 ). A furanonaphthoquinone-based small molecule, AS4583 was identified as an MCM2 inhibitor through phenotypic screening and target deconvolution ( 231 ).…”
Section: Inhibitors Targeting Ssa and Alt-nhej (Tmej) Pathwaysmentioning
confidence: 99%